Found in Translation: Collaborative Contemplations of Tibetan Buddhism and Western Science - Gray, Kelsey M.; Namgyal, Dadul; Purcell, Jeremy; Samphel, Tsondue; Sonam, Tenzin; Tenzin, Karma; Tsering, Dawa; Worthman, Carol M.; Eisen, Arri (Frontiers in Communication, 2020)
Development of an inclusive scientific community necessitates doing more than simply bringing science to diverse groups of people. Ideally, the sciences evolve through incorporation of diverse backgrounds, experiences, and worldviews. Efforts to promote inclusion of historically underrepresented racial, ethnic, cultural, religious, gender, and socioeconomic groups among science scholars are currently underway. Examination of these efforts yields valuable lessons to inform next steps in engaging diverse audiences with science. The Emory-Tibet Science Initiative may serve as one example of such efforts. The Dalai Lama invited Emory University to develop and teach a curriculum in Western science to Tibetan Buddhist monks and nuns. As the science curriculum has been taught and refined over the past decade, monastic scholars increasingly have taken ownership of the material. As Western scientific ideas and practices take hold in this setting, the experiences of monks and nuns offer unique insights into the process of translation, modes of communication, and long-term impacts of integrating diverse systems of knowledge. Given that the dominant language of science is English, Tibetan interpreters have been essential throughout the implementation of this project. Through the process of translating scientific terms we have considered differences in how words categorize, and therefore how we conceptualize, the world. We have moved toward comprehensive, culturally-responsive communication where scientific language is used as a tool to build and strengthen connections between monastics and their local and global communities. The intertwining of these complementary systems of knowledge iteratively informs translation, modes of communication, and broader impacts in the community.